Effect of environmental variables and their interaction on gordiid hairworm larvae (Nematomorpha). (23rd August 2021) - Achiorno, C.L.; Minardi, G.; Ferrari, L.
Abstract: The different stages of the life cycle of parasites are important components of ecosystems. Changes in environmental conditions may affect free-living stages, host–parasite interactions and ecosystem functioning. The larvae of Chordodes nobilii, which belongs to the parasitic phylum Nematomorpha, are susceptible to extreme temperatures and different pollutants, but the effects of pH and moderate temperature variations have not been evaluated yet. Our objective was to assess the effect of temperature, pH and their interaction on the infectivity of C . nobilii larvae to Aedes aegypti larvae over time. Larvae were treated with factorial combinations of temperature (18, 23 and 28°C), pH (7, 8 and 9) and time periods (24 and 48 h). Results show a highly significant interaction among all variables. The highest infectivity was recorded at 18°C and pH 7 at 24 and 48 h, and the lowest one at 28°C and pH 8 at 24 and 48 h. Infectivity differed significantly among the three temperatures only at pH 8 and 48 h, decreasing with increasing temperature. Our study is the first report of the effect of pH on a Nematomorpha species and suggests that the infectivity of C . nobilii larvae may be affected negatively by an increase in temperature and its interaction with pH and time. Since parasites must be considered for a better understanding of the effects of stressors on freshwater ecosystems, our results may help in the design and analysis of studies of anthropogenic impact.